Rationing in a pandemic: lessons from Italy - Craxì, L; Vergano, M; Savulescu, J; Wilkinson, D (Springer, 2020)
In late February and early March 2020, Italy became the European epicenter of the COVID-19 pandemic. Despite increasingly stringent containment measures enforced by the government, the health system faced an enormous pressure, and extraordinary efforts were made in order to increase overall hospital beds’ availability and especially ICU capacity. Nevertheless, the hardest-hit hospitals in Northern Italy experienced a shortage of ICU beds and resources that led to hard allocating choices. At the beginning of March 2020, the Italian Society of Anesthesia, Analgesia, Resuscitation, and Intensive Care (SIAARTI) issued recommendations aimed at supporting physicians in prioritizing patients when the number of critically ill patients overwhelm the capacity of ICUs. One motivating concern for the SIAARTI guidance was that, if no balanced and consistent allocation procedures were applied to prioritize patients, there would be a concrete risk for unfair choices, and that the prevalent “first come, first served” principle would lead to many avoidable deaths. Among the drivers of decision for admission to ICUs, age, comorbidities, and preexisting functional status were included. The recommendations were criticized as ageist and potentially discriminatory against elderly patients. Looking forward to the next steps, the Italian experience can be relevant to other parts of the world that are yet to see a significant surge of COVID-19: the need for transparent triage criteria and commonly shared values give the Italian recommendations even greater legitimacy.